PENGARUH SISTEM PENGENDALIAN INTERNAL, KEMAMPUAN DAN KINERJA SUMBER DAYA MANUSIA DALAM MENGATASI RISIKO KESALAHAN - Muhammad Syahril Alhadi; Maulidia, Rahma; Yantiana, Nella (Universitas Lancang Kuning, 2024)
Internal errors are the most avoided thing in companies and government organizations. Internal errors cause losses to the organization such as damaging the company's reputation, reducing customer trust, and can even cause the company to go bankrupt. Several factors cause internal errors such as a company's poor internal control system, employee abilities that do not match their field, slow employee performance due to lack of motivation, and so on. To overcome this risk, it is necessary to carry out effective prevention to avoid this risk and to ensure the long-term stability of the organization. The purpose of this article is to review the influence of internal control systems, capabilities and human resource performance in overcoming the risk of errors in companies. In this article the researcher uses a qualitative approach using previous research data. The originality of this research lies in the fact that minimal studies have been carried out. The research results indicate that the internal control system can overcome the risk of error, the ability of human resources can overcome the risk of error, and the performance of human resources can overcome the risk of error. The implication is that this research only focuses on internal errors, the capabilities and performance of human resources in overcoming the risk of errors. There needs to be further research to analyze from different aspects in order to complete this research.